Effect of Mitral Valve Leaflets Excursion on Mitral Valve area after Percutaneous Trans- Venous Mitral Commissurotomy (Cardiovascular Journal, 2017)
Background: Aim of our study was to predict the effect of mitral valve leaflets excursion on mitral valve area following percutaneous transvenous mitral commissurotomy PTMC in patients of mitral stenosis.Methods: Total 70 patients with severe mitral stenosis who underwent PTMC were enrolled in the study.Transthoracic echocardiography was done the day before PTMC and 24-48 hours after PTMC. Mitral valve area, anterior and posterior leaflets excursion were recorded. The relation between leaftlet excursion and mitral valve after PTMC was evaluated.Results: Following PTMC there were significant increasein anterior leaflet excursion from 1.9 ± 0.2 to 2.3 ± 0.2cm (p